Room Temperature Palladium‐Catalyzed Decarboxylative Acyl/Aroylation using [Fe(III)(EDTA)(η2‐O2)]3− as Oxidant at Biological pH. Issue 4 (22nd February 2013) - Sharma, Sugandha; Khan, Imran A.; Saxena, Anil K.
Abstract The purple‐coloured iron peroxo complex [Fe(III)EDTA(η2‐O2)]3− as a novel reagent system for Pd‐catalyzed decarboxylative ortho‐acylation of acetanilides with α‐oxocarboxylic acids at room temperature in aqueous media has been realized. This reaction provides an effective access to ortho‐acylacetanilides under mild conditions.